Pathology of Solid Organ Transplantation - Liapis, Helen; Wang, Hanlin L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Because of progress in diagnostic transplantation pathology interpretation of transplant biopsies is increasingly becoming an attractive field for general surgical pathologists. The book focuses on the pathology of transplantation in the following organs: kidney, liver, lungs, heart, pancreas and small intestine. An introductory section addresses common entities that may complicate all transplant recipients such as infections, post-transplant lymphoproliferative disease and graft versus host disease, followed by 6 sections with detailed manifestations of rejection in each organ. This comprehensive, well-illustrated book serves the needs and meets the requirements of pathologists in training and those practicing in centers with limited volume of transplant biopsies in daily practice.
Introductory Section -- History of Organ Transplantation -- Immunology of Organ Transplantation or Mechanisms of Allograft Rejection -- Current Concepts of Immunosuppression and Side Effects -- Common Infections in Transplants Including Clinical and Pathologic Features of Bacterial, Viral (CMV, BK, Adenovirus, and Herpes) and Fungal Infections (Including Histoplasma, Aspergillus, and Others). -- Posttransplant Lymphoproliferative Disorder and Other Neoplasms in Transplant Recipients -- Graft-versus-Host Disease in Transplant Recipients -- Kidney -- Liver -- Lung -- Heart -- Small Intestine -- Pancreas.
Keywords: Pathology; Pathology